Possible Alterations in β-Synuclein, the Non-Amyloidogenic Homologue of α-Synuclein, during Progression of Sporadic α-Synucleinopathies - Fujita, Masayo (Molecular Diversity Preservation International (MDPI), 2012)
α-Synucleinopathies are neurodegenerative disorders that are characterized by progressive decline of motor and non-motor dysfunctions. α-Synuclein (αS) has been shown to play a causative role in neurodegeneration, but the pathogenic mechanisms are still unclear. Thus, there are no radical therapies that can halt or reverse the disease’s progression. β-Synuclein (βS), the non-amyloidogenic homologue of αS, ameliorates the neurodegeneration phenotype of αS in transgenic (tg) mouse models, as well as in cell free and cell culture systems, which suggests that βS might be a negative regulator of neurodegeneration caused by αS, and that “loss of function” of βS might be involved in progression of α-synucleinopathies. Alternatively, it is possible that “toxic gain of function” of wild type βS occurs during the pathogenesis of sporadic α-synucleinopathies, since tg mice expressing dementia with Lewy bodies-linked P123H βS develop progressive neurodegeneration phenotypes, such as axonal pathology and dementia. In this short review, we emphasize the aspects of “toxic gain of function” of wild type βS during the pathogenesis of sporadic α-synucleinopathies.